2016
DOI: 10.2320/matertrans.m2016124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen on the Microstructure and Hardness of High-Carbon High-Speed Tool Steel Type Alloys

Abstract: The effect of nitrogen addition on the microstructure formation and hardness during solidi cation and heat treatment was investigated and the possibility of nitrogen as an alloying element was discussed in terms of alloy chemistry for high-carbon high-speed tool steel type cast alloys. Nitrogen with a concentration from 48 ppm to 1542 ppm was successfully introduced by mixing Cr 2 N into a molten alloy. Analysis of the diffraction pattern revealed that the primary V 2 CN carbonitride crystallized upon the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Compared to layered M 2 C, fibrous M 2 C is easily disintegrated into more stable M 6 C and MC during forging and annealing. Hara et al [64] investigated the effect of N on the solidification structure of high-speed steel. They successfully introduced nitrogen at a concentration ranging from 48 ppm to 1542 ppm, as found in high-speed steel, by mixing Cr2N into the molten alloy.…”
Section: Nitrogenmentioning
confidence: 99%
“…Compared to layered M 2 C, fibrous M 2 C is easily disintegrated into more stable M 6 C and MC during forging and annealing. Hara et al [64] investigated the effect of N on the solidification structure of high-speed steel. They successfully introduced nitrogen at a concentration ranging from 48 ppm to 1542 ppm, as found in high-speed steel, by mixing Cr2N into the molten alloy.…”
Section: Nitrogenmentioning
confidence: 99%
“…As the solubility product of VN is much smaller than that of VC, vanadium nitride is much more thermodynamically stable than vanadium carbide in austenite 24,25) and then the former is preferentially precipitated. Through the thermodynamic calculation and experimental measurement, a certain amount of N in HSS promotes the formation of primary M(C,N) which includes higher content of N than that of C, while in the eutectic MC, the content of N is much fewer than that of C. [26][27][28] The maximum contents of V, C and N in MC are 77.89%, 9.20% and 4.05% respectively and the average contents of Cr, Mo and W in MC are about 5.60%, 7.19% and 9.57% respectively. In fact, a certain difference of the contents of alloy elements in primary lumpy MC and eutectic strip-like MC occurs and a new scale bar of V content is used to clearly display the difference as shown in Fig.…”
Section: Carbide Compositionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24] Recent studies have shown that adding N to HSS could produce some beneficial effects on its properties. For instance, Hara et al [25] and Halfa et al [26] reported that N-alloying could increase the secondary hardness of high-carbon HSS and M41 HSS owing to the precipitation of carbonitrides. Mattar et al reported that the room-temperature wear resistance of M41 HSS was improved by N-alloying owing to the increase of hardness and precipitate concentration.…”
Section: Introductionmentioning
confidence: 99%